Disability in Africa : Inclusion, Care, and the Ethics of Humanity - Hamel, Nic; Falola, Toyin (Book collections on Project MUSE., 2021)
"While the disability rights movement of recent decades has a rich and well-documented history, it is a history mostly focused on the Global North. Disability in Africa presents an interdisciplinary approach to cultural, health, and policy challenges that disability issues have raised throughout the African continent. The volume draws on the achievements of disability studies while acknowledging the demands and challenges of particular African contexts. The authors bring diverse methodological approaches and expertise to bear on these issues, ranging from anthropology and bioethics to special education and community rehabilitation. Essays consider indigenously African definitions of disability as well as exploring disability at the intersection of poverty, geography, and globalized biopolitics. Contributors analyze the difficulties of implementing disability policy across the continent while also being mindful of successful approaches taken at local, national, and international levels. Disability in Africa thus charts new avenues for disability studies research in and about Africa"--